The practices of green maintenance at Islamic student residential building in east coast region - Mohammad Affendy, Omardin; Mohd Nasir, Ayub; Liu, Yao; Diyana, Kamarudin (Universiti Teknologi MARA (UiTM) Kedah, 2018)
The green maintenance practices in Malaysia based on the need of occupants and user activities. In recent years, green maintenance concept has become the common interest of numerous disciplines. The concept of green maintenance for Islamic approach in Islamic student's residential building were not in appropriate, The need to have a well practices in green maintenance for the Islamic student residential building. Howevel', nlost of the buildings were poorly managed and not well green application practices relation with comfortability and safety adopt. The green maintenance in practices integrated within sustainability features to produce condusive safety in building. lntervie,vs 'vas conducting among of 30 students being interviewed. The survey to identify their knowledge awareness in term of green maintenance and safety practices. The results indicate that the need to improve the green maintenance practices at the student's residents and reduce the uncomfortability to the student's residents due to wealth their day life activities.